Library Science Ethics: A Study on the Ethical Perceptions and Behaviors of Staff in University Libraries - Aksakallı, Selim (Information World, 2025)
This study aims to present an introduction to the book titled “Library Ethics: A Study on the Ethical Perceptions and Behaviors of Personnel in University Libraries.” The work seeks to enhance ethical awareness in the field of library science and examine the current ethical perceptions. The book consists of four chapters: the first chapter addresses the concepts of ethics and morality as well as ethical theories, while the second chapter discusses the role of professional ethics and ethical rules in enhancing the reputation of the profession. The third chapter examines library science ethics and professional ethical principles, and the fourth chapter presents the findings of a study on the ethical perceptions of staff in university libraries. The book emphasizes that ethical issues are not sufficiently addressed in Turkish university libraries and highlights the need to increase awareness of professional ethics.
Keywords: Ethics; professional ethics; library science ethics